Estudos botânicos nas ilhas de Maiandeua - Algodoal (PA). o pólen das famílias sapindaceaee solanaceae da restinga de Algodoal-Pa - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1996)
The pollen morphology of the species Cupania diphylla Val., Cupania sp., Matayba discolor (Spreng.) Radlk., Paullinia pinnata L., Pseudima frutescens (Aubl.) Radlk, Toulicia acutifolia Radlk, (Solanaceae), Schwenkia americana L., Solanum paludosum Moric. and Solanum straminofolium Jacq (Sapindaceae), which occur predominantly on the island of Maiandeua, located on the coast of Pará, in the municipality of Maracanã. To prepare the slides, adult flower buds were collected from exsiccata of the MG herbarium (Museu Paraense Emílio Goeldi), and then acetolysis was performed. The pollen grains were measured, described and photomicrographed. It was observed that the pollen grains of Solanaceae species are small, isopolar, 3-colporate, amb varying from circular to triangular, the shape from subprolate to prolate and the surface from psyllate to punctate. Those of Sapindaceae are at the slide preparation stage.
Botanical studies on the islands of Maiandeua - Algodoal (PA). the pollen of the families sapindacea and solanaceae from the sandbank of Algodoal-Pa
Keywords: Sapindaceaee; Solanaceae; Restinga; Pólen; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA::MORFOLOGIA VEGETAL